What to choose when the best preference is not available: does the Nile tilapia follow a linear sequence of preferences? - Maia, C. M. [UNESP]; Volpato, G. L. [UNESP] (Wiley, 2019)
Preference tests have been applied to detect better welfare conditions for the animals. Among these tests, the available choice options are variable and thus, the best preferences may not be included. Considering welfare purposes, it is relevant to know whether the animal would select a second option as a preference in this situation, which could be offered when the best preferences are not available. Here, we evaluate whether Nile tilapia fish (Oreochromis niloticus) follow a linear sequence of preference responses when selecting background colors. We found that when a fish's most preferred option was unavailable, this animal selected less intensely one of the remaining options as a new preference. However, surprisingly, the new preference was not predominantly the previously second selected option. Such a finding could not be explained in terms of intensity of the responses when the mostly preferred option was available or not. These data corroborate that changing the scenario where the preference is being tested affects animal decision for the remaining available options. That is, the environmental context is important for the fish to evaluate their preferred options.
Keywords: intensity response; preference context; second option; unavailable preference